PRELIMINARY OBSERVATIONS ON THE FISHERY OF BOMBAYDUCK HARPODON NEHEREUS IN THE GULF OF KUTCH - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
The fishery for Bombayduck in the Gulf of Kutch is well organised and is conducted on the pattern of that of Bombay and Saurashtra coasts. The total Bombayduck landings from the gulf are estimated between 8,000 to 10,000 tonnes; the major landing centres being Modhwa, Navinar, Bhadreshwar and Takkara. The boats engaged are Machchwa type and nonmechanised. The bag net, locally known as ’Gunja,’ is used, which is similar to the ’dol’ net. Raciation studies on samples from Kutch and Jaifrabad revealed that the fish from these places differ significantly in 6 morphometric characters